The Role of Evidence-Based Research in the Decision-Making Process as Perceived by Local Board of Education Policymakers in West Virginia - Hoylman, Elizabeth Anne (2017)
This non-experimental, descriptive study explored the perceptions of PK-12 policymakers in West Virginia regarding the sources of information they use in the decision-making process; whether and how evidence-based research is relied upon; whether evidence-based research is considered credible and usable; and what barriers, facilitators, and demographic data may play roles in the decision-making process. Data were collected from a 15-question researcher-created survey administered to nearly 200 county board of education members. Results indicated that while policymakers think evidence-based research is important, they nonetheless use it less than other types of information. Consumers consider research reports too lengthy. Respondents indicated they strongly agreed that evidence-based research is vital to decision-making; however, professional journals, a widely accepted source for disseminating evidence-based research, were among the least consulted information sources by respondents. Intermediaries, in the form of trusted individuals such as the superintendent, were among the most frequently consulted, most heavily relied upon, and found to be among the most credible and most useful information sources by survey respondents. Therefore, research must get into the hands of intermediaries, preferably in the form of brief, non-ambiguous summaries, so the work of researchers can be passed along to policymakers and used to guide decisions